1994
DOI: 10.1080/10408399409527653
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic browning reactions in apple and apple products

Abstract: This review examines the parameters of enzymatic browning in apple and apple products that is, phenolic compounds, polyphenoloxidases, and other factors (ascorbic acid and peroxidases), both qualitatively and quantitatively. Then the relationships between intensity of browning and the browning parameters are discussed, including a paragraph on the methods used for browning evaluation. Finally, the different methods for the control of browning are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
374
4
32

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 549 publications
(427 citation statements)
references
References 353 publications
17
374
4
32
Order By: Relevance
“…The apple juice obtained from Jonagold apples by pulping and straight pressing had 10% of the antioxidant activity of fresh apples, while the juice obtained after pulp enzyming had only 3% of the antioxidant activity. After pulp enzyming, the juice contained 31% less phloridzin, 44% less chlorogenic acid, and 58% less catechin.Apple mash undergoes the oxidative reaction very easily which results in the oxidation of phenolic compounds into o-quinones, which subsequently polymerise into complex dark coloured pigments (Nicolas et al 1995).To satisfy consumers' growing demand for the products containing bioactive components, certain protection of phenolics in apple juices is of vital importance.To reduce apple pulp browning , chemical antioxidant was used (Lee & Whitaker 1995). Considerable research was conducted into the natural antioxidant substances, such as honey (Oszmiański et al 1990), pineapple juice (Lozano-de-Gonzalez et al 1993), and rhubarb juice (Son et al 2000).…”
mentioning
confidence: 99%
“…The apple juice obtained from Jonagold apples by pulping and straight pressing had 10% of the antioxidant activity of fresh apples, while the juice obtained after pulp enzyming had only 3% of the antioxidant activity. After pulp enzyming, the juice contained 31% less phloridzin, 44% less chlorogenic acid, and 58% less catechin.Apple mash undergoes the oxidative reaction very easily which results in the oxidation of phenolic compounds into o-quinones, which subsequently polymerise into complex dark coloured pigments (Nicolas et al 1995).To satisfy consumers' growing demand for the products containing bioactive components, certain protection of phenolics in apple juices is of vital importance.To reduce apple pulp browning , chemical antioxidant was used (Lee & Whitaker 1995). Considerable research was conducted into the natural antioxidant substances, such as honey (Oszmiański et al 1990), pineapple juice (Lozano-de-Gonzalez et al 1993), and rhubarb juice (Son et al 2000).…”
mentioning
confidence: 99%
“…Additionally as it is indicated in Table 1, even lowering pH to 4.5 in HPP treated samples, which was suggested to minimize PPO activity (Whitaker 1994), failed to prevent browning. Nevertheless, it has also been reported that PPO in apple is quite tolerant to acidity and at pH value of 3.0 retains 40 % of its maximum activity (Nicolas et al 1994). In fact when aiming at enzyme inactivation by applying high pressure technology, the pressure requirements vary depending on the enzyme.…”
Section: Color Evaluationmentioning
confidence: 99%
“…Pada penelitian lain juga pernah disebutkan oleh Richardson dan Hyslop (1985) bahwa enzim PPO inaktif pada pH 3. Meskipun demikian, Nicolas et al (1994) menyebutkan bahwa PPO pada buah apel lebih toleran terhadap asam, dimana pada pH 3 aktivitas enzim PPO dihambat hingga 60%. Tranggono dan Sutardi (1990) menyatakan asam sitrat tidak hanya menurunkan pH medium, tetapi juga terjadi ikatan dengan Cu ++ pada enzim.…”
Section: Pengamatan Warna Potongan Buah Apelunclassified